PERAN GAYA KEPEMIMPINAN DAN KOMUNIKASI DALAM MENINGKATKAN MOTIVASI KERJA KARYAWAN PADA UMKM KULINER DI KOTA CIREBON - Dienisa Etka Maharani Zahara; Nuraeni Qusnul Khotimah; Bima Rahmadian; Angga Prayogi Briliyanto (STKIP Subang, 2026)
Employee motivation is crucial for the success of any business, including micro, small, and medium enterprises (MSMEs). In Cirebon City, increasingly fierce competition in the culinary business requires MSMEs to maintain the enthusiasm and responsibility of their employees serving customers. This study aims to examine the role of leadership and communication styles in improving employee motivation in culinary MSMEs in Cirebon City. This study used a qualitative approach with interviews as the primary data collection technique. Ten informants residing in Cirebon City, consisting of employees and MSME owners/managers, were selected using purposive sampling based on their work experience. Interview data were analyzed using thematic analysis techniques, namely through transcription, coding, grouping themes, and drawing conclusions. The results showed that the form of leadership most preferred by employees was not simply giving instructions, but when the business owner directly worked with employees during peak customer hours and directly modeled correct work techniques rather than simply reprimanding them, so that employees felt supported and did not work alone. The most memorable forms of appreciation for employees are generally not formal bonuses, but rather personal things like the convenience of changing shifts or taking time off, holiday allowances, and even invitations to vacation together out of town, paid for by the business owner. Meanwhile, the most common communication problem is the lack of structured information channels: operational instructions and information such as stock, prices, and order details are often only conveyed verbally and suddenly during peak business hours, which can lead to minor errors, such as mixed up customer orders. This study concludes that leadership style and communication support each other in building work motivation in MSME employees and is expected to provide input for small business owners in Cirebon in managing their employees.